Doping controlled roughness and defined mesoporosity in chemically etched silicon nanowires with tunable conductivity - HOLMES, JUSTIN DEREK (My University, 2013)
By using Si(100) with different dopant type (n(++)-type (As) or p-type (B)), we show how metal-assisted chemically etched (MACE) nanowires (NWs) can form with rough outer surfaces around a solid NW core for p-type NWs, and a unique, defined mesoporous structure for highly doped n-type NWs. We used high resolution electron microscopy techniques to define the characteristic roughening and mesoporous structure within the NWs and how such structures can form due to a judicious choice of carrier concentration and dopant type. The n-type NWs have a mesoporosity that is defined by equidistant pores in all directions, and the inter-pore distance is correlated to the effective depletion region width at the reduction potential of the catalyst at the silicon surface in a HF electrolyte. Clumping in n-type MACE Si NWs is also shown to be characteristic of mesoporous NWs when etched as high density NW layers, due to low rigidity (high porosity). Electrical transport investigations show that the etched nanowires exhibit tunable conductance changes, where the largest resistance increase is found for highly mesoporous n-type Si NWs, in spite of their very high electronic carrier concentration. This understanding can be adapted to any low-dimensional semiconducting system capable of selective etching through electroless, and possibly electrochemical, means. The process points to a method of multiscale nanostructuring NWs, from surface roughening of NWs with controllable lengths to defined mesoporosity formation, and may be applicable to applications where high surface area, electrical connectivity, tunable surface structure, and internal porosity are required.
PUBLISHED
Keywords: Porous silicon; Crystalline silicon; Anodic formation; Arrays; Nanostructures